Returning Government Policy for Poverty Reduction in Aceh - Ernita Dewi; Munawiah Munawiah; Siti Nurzalikha (Budapest International Research and Critics University, 2018)
Aceh and Bengkulu are included in the top list of the poorest regions of Sumatra, in fact, are in the top ten in Indonesia. Aceh with a large budget both from APBA, special autonomy funds and oil and gas revenue sharing funds, but poverty is still a fetter for the people of Aceh. It is not wrong if many question the government policies that are always echoed to alleviate poverty. This paper wants to describe in detail the government policies in alleviating poverty, it is right on target or it still dwells on the poverty alleviation discourse, and programs that are proclaimed are only limited to ideals that are not in accordance with the reality and needs of society.